PROTEKSI PASIF KEBAKARAN PADA STUKTUR PENOPANG PIPA PROSES DENGAN EPOXY INTUMESCENT - Sulardi Sulardi (IDENTIFIKASI, 2020)
The purpose of this study is to provide a description of passive fire protection material specifications that are suitable and suitable for pipe rack protection, pipe support and hanger pipe support hotline hydrocarbons and working methods of application of epoxy intumescent material. The research method used is the applied research method with a case study approach to the difficulty of handling sub-standard conditions at the Balikpapan I refinery. The research was conducted for 6 months and an observation period of 2 years. The results showed that the epoxy intumescent material specifications could be applied well and safely with an application thickness of 8.13 mm for a 1.5-hour fire rating according to API Standard 2218 and covered insurance findings at the Balikpapan refinery 1. The success of the intumescent epoxy application replaced the fireproofing material based on cementitious this can be replicated to overcome similar problems at other process unit refineries that experience similar problems.